2015
DOI: 10.1111/geb.12312
|View full text |Cite
|
Sign up to set email alerts
|

The weakness of evidence supporting tropical niche conservatism as a main driver of current richness–temperature gradients

Abstract: Aim Geographical variations in species richness are highly correlated with current temperature. The tropical niche conservatism hypothesis proposes that this relationship is driven by the evolutionarily conserved ancestral tolerances of species to the warm environments in which most clades originated. The hypothesis predicts that the slope of the richness–temperature gradient is positively related to the temperature of the period during which the clade originated. Here, we test this prediction for bird and mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…By not analysing local communities, these studies have been unable to adequately assess the potential influence of environmental factors on SR, PD or lineage diversity (cf. Boucher‐Lalonde et al ., ). Those studies that have taken a community approach have had sparse sampling across the Southern Hemisphere, particularly in South America (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…By not analysing local communities, these studies have been unable to adequately assess the potential influence of environmental factors on SR, PD or lineage diversity (cf. Boucher‐Lalonde et al ., ). Those studies that have taken a community approach have had sparse sampling across the Southern Hemisphere, particularly in South America (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, Boucher‐Lalonde et al . () found that once positive relationships between species richness and current climate are taken into account, the temperature and presumably latitude, at which a clade originates has little influence on its species richness, which the authors take as evidence against the TCH. Other studies have also found results that are contradictory to patterns expected under the TCH, both at a global scale (Jansson et al ., ) and in South America (Segovia et al ., ; Qian, ; Tiede et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, this hypothesis predicts that species diversity for a given clade will be low in regions where the climate conditions deflect from the clade’s ancestral niche, because species have difficulties to evolve adaptions to new climatic niches 8 9 10 . According to niche conservatism hypothesis, species originated in tropical regions tend to show strong positive diversity-temperature relationship while clades originated in temperate regions show negative diversity-temperature relationship 11 12 13 . However, it still remains controversial whether contemporary climate drives species diversity through the control of ambient energy or through niche conservatism.…”
mentioning
confidence: 99%